Multistage sampling for genetic studies - Elston, Robert (Henry Stewart Talks, 2007)
Classical paradigm for rare monogenic diseases, Multistage designs for association studies, common complex diseases, Random and multiplex family samples, case-control samples, Genetic epidemiology: segregation analysis, linkage analysis, association analysis, Sampling to minimize cost, Multiphase analysis to increase power, multiple comparisons
Archived at 2021/02/25